SERVICE QUALITY, CUSTOMER SATISFACTION, AND LOYALTY IN EVENT PLANNING: A STUDY OF INDIAN WEDDINGS - Deshpande, Sunil Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
As one of the most well-known Indian wedding businesses, which is highly opulent and highly important in itself, it needs to have outstanding service quality to remain customer-loyal and entertained. In this research, service quality dimensions of tangibility, dependability, responsiveness, assurance, and empathy regarding the Indian wedding planning industry are studied on how they affect customer happiness as well as loyalty. This research collection gathered data from 420 customers who used wedding event planning services in India with the help of quantitative research. Statistical methods used to evaluate associations between the variables include multiple regression, Pearson correlation, and structural equation modeling (SEM). The results indicate that all five service quality aspects have a significant impact on customer satisfaction, which in turn leads to mediation of customer satisfaction on the relation between service quality and customer loyalty. A lesson to be learned from these results is that event coordinators need to focus on providing and tailored services to each client whose cultural and personal preferences are taken into account. may also help them increase customer happiness, build loyalty, and get a competitive edge in the ever-changing Indian wedding industry. The results presented in this study serve as an addition to the very little body of empirical research in the service quality of the event planning sector and offer some useful advice for the practitioners, assuming that they aim to improve service quality and stand successful in the long term.